MOTHERS' SENSITIVITY TO THEIR INFANTS' NEEDS: AN EXPLORATION OF INFLUENCING FACTORS IN THE FIRST SIX MONTHS - Dewi Srinatania (rifascholarpublisher.com, 2026)
Background: The first six months of life are a critical period in human development. Maternal sensitivity—defined as a mother’s ability to respond promptly and appropriately to her infant’s needs with warmth and attention—plays a key role in establishing a secure mother–child bond, which is essential for the child’s future social and emotional development. Objective: This study aimed to identify factors influencing maternal sensitivity in mothers with infants aged 0–6 months. Methods: A descriptive quantitative design was employed with 113 respondents selected through non-probability sampling. Inclusion criteria were mothers with infants aged 0–6 months. Maternal sensitivity was measured using the Nursing Child Assessment Teaching Scale (NCAST) questionnaire. Statistical analysis was conducted to determine the association between demographic factors and maternal sensitivity. Results: The number of children and family income were found to have a significant association with maternal sensitivity (p < 0.05). Other factors examined did not show significant relationships. Conclusion: The study concludes that the number of children and family income are the most influential factors affecting maternal sensitivity among mothers of infants aged 0–6 months. Interventions to enhance maternal sensitivity should consider these determinants.